2021
DOI: 10.3389/fphar.2021.733075
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive NK Cell Therapy Modulated by Anti-PD-1 Antibody in Gastric Cancer Model

Abstract: Recently, adaptive NK cell therapy has become a promising treatment but has limited efficacy as a monotherapy. The identification of immune checkpoint inhibitor (ICI) molecules has opened a new horizon of immunotherapy. Herein, we aimed to demonstrate the cytotoxic effects of a polytherapy consisting of ex vivo expanded IL-2-activated NK cells combined with human anti-PD-1 antibody as an important checkpoint molecule in a xenograft gastric cancer mouse model. EBV-LCL cell is used as a feeder to promote NK cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 78 publications
(75 reference statements)
1
8
0
Order By: Relevance
“…Circulating CD4+ T cells can target cancer cell surface antigens and activate peripheral blood CD8+ T cells, allowing them to enter the tumor microenvironment and kill cancer cells [ 63 , 64 ]. Bihui et al confirmed that NK cells have strong antitumor activity and can effectively eliminate and inhibit gastric cancer cells [ 65 , 66 ]. Our data indicated that with high expression of MAGEA11 , the immune microenvironment inhibits the infiltration of immune cells, creating an environment for immune escape tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating CD4+ T cells can target cancer cell surface antigens and activate peripheral blood CD8+ T cells, allowing them to enter the tumor microenvironment and kill cancer cells [ 63 , 64 ]. Bihui et al confirmed that NK cells have strong antitumor activity and can effectively eliminate and inhibit gastric cancer cells [ 65 , 66 ]. Our data indicated that with high expression of MAGEA11 , the immune microenvironment inhibits the infiltration of immune cells, creating an environment for immune escape tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Following preclinical research, the synergy potential of targeted antibodies with NK cell therapy should be further investigated in clinical trials. Our research group demonstrated that pretreated checkpoint blockade NK cells could effectively enhance the NK cells’ trafficking in TME and beneficially reduce the tumor cell mitosis in gastric cancer xenograft model ( 189 ). However the same results was not achieved in chemo immune cell therapy of Intratumoral injection of NK cells in combination with capecitabine in gastric cancer xenograft model in the other study of our group ( 190 ).…”
Section: Antibodies Increase Nk Cell Cytotoxicity Against Colorectal ...mentioning
confidence: 99%
“…In addition, the cytokines can activate NK cells and promote their proliferation to enhance anti-tumor activity, such as IL-2, IL-12, IL-15, and IL-18 ( 186 188 ). NK cells activated by IL-2 which combined with anti–PD-1 can inhibit tumor growth in xenograft GC models ( 189 ). In addition, IL-15 can increase the infiltration of NK cells in the tumor ( 190 ) and improve the survival rate in the treatment of GC liver metastasis–bearing mice ( 191 ).…”
Section: Immunotherapy Targeting Nk Cellsmentioning
confidence: 99%